2011
DOI: 10.1128/iai.00130-11
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Bacillus Spores Expressing Toxin A Peptide Repeats Protects against Infection with Clostridium difficile Strains Producing Toxins A and B

Abstract: ). Thus, although many strains produce both toxins, antibodies to only toxin A can mediate protection. Animals vaccinated with recombinant spores were fully able to survive reinfection, a property that is particularly important for a disease with which patients are prone to relapse. We show that mucosal immunization, not parenteral delivery, is required to generate secretory IgA and that production of these neutralizing polymeric antibodies correlates with protection. This work demonstrates that an effective v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
94
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 44 publications
3
94
2
4
Order By: Relevance
“…In both mouse and hamster infection models of CDI, preventing infection-associated mortality is seen as an important metric of vaccine efficacy (12,13,22,23,(58)(59)(60)(61)(62)(63)(64)(65)(66). Upon challenging pRBD-NQ-immunized animals with a lethal dose of spores, we observed 90% and 50% protection against homologous and heterologous strains, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…In both mouse and hamster infection models of CDI, preventing infection-associated mortality is seen as an important metric of vaccine efficacy (12,13,22,23,(58)(59)(60)(61)(62)(63)(64)(65)(66). Upon challenging pRBD-NQ-immunized animals with a lethal dose of spores, we observed 90% and 50% protection against homologous and heterologous strains, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…42 This observation underscores the exploration of C. difficile vaccines as a novel treatment/prevention modality. [43][44][45][46] Our current model is characterized by the acute development of disease and employs naĂŻve mice, and thus C. difficile-specific adaptive responses are not thought to play a role. However, since this model can be manipulated such that the disease is not uniformly fatal (unlike the hamster model of disease), it remains to be determined if this model will be useful for studying adaptive immunity in CDI.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, RBDs of TcdA and TcdB have been evaluated for their ability to induce protective immunity. 25,[32][33][34] Recent studies have indicated that the N-terminal GT domain of TcdB can serve as an excellent immunogen. 35,36 This notion was initially supported by our recent construction of a chimeric recombinant vaccine against TcdA and TcdB, i.e., cTxAB, in which the original RBD of a full-length TcdB was replaced with the corresponding portion of TcdA.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Formaldehyde-inactivated native C. difficile toxins have been reported to be well tolerated and able to induce protective immunity in CDI in humans. 22,30,31 However, chemical toxoiding requires establishing rigorous conditions to eliminate toxicity in the final drug product while minimizing any loss of immunogenicity.…”
Section: Introductionmentioning
confidence: 99%